PERFORMANCE OF FEMALE DUCKLING WHICH MAINTAIN BASED ON SMALL, BIG AND MIXED GROUPS OF HATCHING WEIGHT - Komarudin Komarudin; Rukmiasih Rukmiasih; P.S. Hardjosworo (Pusbindiklat - LIPI, 2011)
This research was conducted to determine the effect of maintain method based on small, big and mixed groups hatching weight on performance at the age of six weeks. 122 female Day Old Duck (DOD) were used. The ducks were partitioned based on hatching weight. DOD with more than 42 g was classiﬁ ed as a big group and less or equal to 42 g were classiﬁ ed as small group. Mixed group was taken from those two groups randomly. Feed consumption and conversion, growth and weight of ducks at the age of six weeks were measured. The research used Random Group Analysis. The result showed signiﬁ cant different (P<0,01) of growth and the weight. Feed consumption and conversion of each groups (small, big and mixed) did not showed the differences (P>0,05).Separated maintain method duck based on hatching weight (small and big groups) did not give better performance than mixed group method.